An analysis of shear waves observed in VSP data from the superdeep well at Kola, Russia - Digranes, Per; Kristoffersen, Yngve; Karajev, Nazim (Geophysical Journal International, 1996)
Two VSPs have been analysed from the Kola superdeep borehole, located on the Kola Peninsula. The Kola borehole was drilled down to a depth of 12 260 m and VSPs were recorded in the interval 2150 to 6000 m. The VSPs sample the Proterozoic Pechenga complex, which consists of alternating metasedimentary and metavolcanic layers that range from greenschist to amphibolite-grade facies. The structural dip is 28–45° to the SSW, and a major shear zone (the Luchlompolsky fault) occurs at 4.5 km depth. The VSPs display strong transmitted- and reflected-mode converted energy from structural and lithologic boundaries. A kinematic (traveltime) ray-tracing modelling of the main compressional- ( P -) and shear- ( S -) wave events was performed to define the seismic boundaries. P - and S -wave velocities were estimated from the near-offset data, and V p / V s ratios were related to the lithology. A significant increase in the V p / V s ratio is observed in the main shear zone at 4.5 km depth. Shear-wave splitting is identified by traveltime divergence (different apparent velocites) and orthogonal polarization of S phases in the far-offset VSP. The inferred polarization direction for the fast shear wave is N160°W, clearly observed below 4400 m depth. Two models are suggested to explain the observed shear-wave splitting: intrinsic anisotropy caused by aligned hornblende minerals in the amphibolite-grade facies; and vertical cracks aligned N160°W. The direction of crack alignment is not consistent with the present-day NW-SE maximum compressive stress field. However, it is consistent with the direction of the palaeostress, the direction of crack alignment at the surface and the fast direction obtained from analysis of shear waves in shallow VSPs. The velocity anisotropy is estimated to be 4–5 per cent with a local increase to 10 per cent in the Luchlompolsky fault zone.